Biochemical Traits, 1H NMR Profile and Residual DNA Content of ‘Asprinio’, White Wine from Campania Region (Southern Italy) - Landi, Nicola; Scognamiglio, Monica; Woodrow, Pasqualina; Ciarmiello, Loredana F.; Ragucci, Sara; Clemente, Angela; Hussain, Hafiza Z. F.; Fiorentino, Antonio; Di Maro, Antimo (Foods, 2022)
‘Asprinio’ is a white dry wine characteristic for its acidity and aromatic flavour, known as emerging DOP wine in Southern Italy. Nevertheless, little information is available on the metabolomic profile of this wine. Thus, in this paper we evaluated the colourimetric parameters, 1H NMR profiles and free amino acids content of ‘Asprinio’ wines, bottled by two different wineries (hereafter ‘Asprinio_A’ and ‘Asprinio_B’) collected in 2019 and 2020, using ‘Greco di Tufo’ for comparison. The colourimetric parameters are similar for both ‘Asprinio’ wines and differ from ‘Greco di Tufo’ wines. On the other hand, both 1H NMR and free amino acid content profiles show different chemometric profiles among the three wines analysed, although the profiles are similar for both vintages. Moreover, the multivariate analyses carried out highlight differences between ‘Asprinio_A’ and ‘Asprinio_B’, which exbibit also different residual yeast and plant DNA. Overall, considering that the two-manufacturing wineries use 100% ‘Asprinio’ grape, the difference retrieved between the two ‘Asprinio’ wines could be explained by the different grapevine training systems: ‘vite maritata’ (training system inherited from Etruscans) for ‘Asprinio_A’ and ‘guyot’ for ‘Asprinio_B’.